Preliminary evaluation of F1 generation derived from two common bean landraces (Phaseolus vulgaris) from Nicaragua. Issue 2 (18th February 2013) - Jiménez, Oswalt R.; Korpelainen, Helena; Link, W.
Abstract Germplasm improvement is a conceivable solution for increasing food production in developing countries. The objectives of the present study were to incorporate the genetic diversity of two Nicaraguan common bean landraces into a segregating population and to evaluate its potential as breeding material. Adapted landraces PV0006 and PV0023 were selected as parents for single crosses based on molecular and phenotypic characteristics. The results indicate that we succeeded in reshuffling most of the genetic diversity of both parents into a segregating population. The level of allele recombinations suggests that theoretically between 128 and 1024 different pure lines could be obtained. We found putative associations between alleles and yield‐determinant components. Computer simulations demonstrated that the pedigree method and the marker selection of the most segregating individuals in the F1 generation could improve the genetic gains for yield. These findings expose the potential of this segregating population and the feasibility of local landraces for bean improvement.